Human movement patterns and local spread of COVID-19 - Cowling, Ben (Henry Stewart Talks, 2021)
Observed spreading of SARS-CoV-2 and the R numbers describing it, What are ‘super-spreader events’ (SSEs), Role of SSEs in the local transmission of SARS-CoV-2, Effect of human movement patterns on the incidence of SSEs and overall transmission, Effectiveness of lockdowns in preventing SSEs and reducing transmission, Implications of these findings for public health officials and safety guidelines